Primary breast osteosarcoma in a patient previously treated for ipsilateral invasive ductal carcinoma: An unusual case report with clinical and genomic features - Zhu, Siji; Wang, Haoyu; Lin, Lin; Fei, Xiaochun; Wu, Jiayi (Frontiers in Oncology, 2023)
Primary breast osteosarcoma was a rare subtype of breast malignancy with limited clinical evidence, inadequate biological understandings and unmet treatment consensus. Here we report an unusual case of primary breast osteosarcoma developed at the same quadrant of breast 2 years after initial dissection and radiation of invasive ductal carcinoma. Thorough evaluations of imaging and pathology were conducted while genomic alterations of both primary and secondary tumor, as well as peripheral blood samples were explored through next-generation sequencing technique. Comprehensive review of the current literatures was also performed on this rare malignancy.